2019
DOI: 10.1177/1747021819849512
|View full text |Cite
|
Sign up to set email alerts
|

Re-reconsidering the role of temporal order in spoken word recognition

Abstract: Spoken word recognition models incorporate the temporal unfolding of word information by assuming that positional match constrains lexical activation. Recent findings challenge the linearity constraint. In the visual world paradigm, Toscano, Anderson, and McMurray observed that listeners preferentially viewed a picture of a target word’s anadrome competitor (e.g., competitor bus for target sub) compared with phonologically unrelated distractors (e.g., well) or competitors sharing an overlapping vowel (e.g., su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 34 publications
2
32
2
Order By: Relevance
“…It is the partial activation of such words that is thought to have driven the eye‐movement patterns in Toscano et al's study and the short‐term priming effects of this study. Our results also confirm the eye‐tracking observations that the transposed‐phoneme effect is due to more than vowel position overlap in the transposed words (Gregg et al, in press; Toscano et al, ). They also confirm that two shared phonemes with one phoneme in a different position cause lesser activation of the target words (Toscano et al, ), and that complete phonemic overlap is a necessary condition in order to obtain transposed‐phoneme effects.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…It is the partial activation of such words that is thought to have driven the eye‐movement patterns in Toscano et al's study and the short‐term priming effects of this study. Our results also confirm the eye‐tracking observations that the transposed‐phoneme effect is due to more than vowel position overlap in the transposed words (Gregg et al, in press; Toscano et al, ). They also confirm that two shared phonemes with one phoneme in a different position cause lesser activation of the target words (Toscano et al, ), and that complete phonemic overlap is a necessary condition in order to obtain transposed‐phoneme effects.…”
Section: Discussionsupporting
confidence: 90%
“…At the same time, they showed that competitors without vowel position overlap (LEAF‐FLEA) were not fixated more that unrelated words, thus indicating that positional vowel match is critical in the observation of the transposed‐phoneme effect. As discussed by Gregg et al (in press), such a finding could argue for a special status for vowels that would be processed more rapidly than consonants. Within the framework of the TISK model, the findings of Gregg et al suggest that the position‐independence of phoneme identities might be constrained by the abstract CV‐structure of the stimulus being processing.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…This finding suggests that the transposed-phoneme effect is due to more than just vowel position overlap in the transposed words. The main finding of Toscano et al (2013) that CAT and TACK are confusable words was replicated in a following study by Gregg et al (2019) with a larger set of items. At the same time, Gregg et al (2019) showed that competitors without vowel position overlap (e.g., LEAF-FLEA) were not fixated more that unrelated words.…”
mentioning
confidence: 75%